China's Macroeconomic Outlook Quarterly Forecast and Analysis Report, October 2017 - Center for Macroeconomic Research of, Xiamen University (Current Chinese Economic Report Series,, 2018)
This report is a partial result of the China's Quarterly Macroeconometric Model (CQMM), a project developed and maintained by the Center for Macroeconomic Research (CMR) at Xiamen University. The CMR is one of the Key Research Institutes of Humanities and Social Sciences sponsored by the Ministry of Education of China, focusing on China's economic forecast and macroeconomic policy analysis. The CMR started to develop the CQMM for purpose of short-term forecasting, policy analysis, and simulation in 2005. Based on the CQMM, the CMR and its partners hold press conferences to release forecasts for China' major macroeconomic variables. Since July, 2006, twenty-two quarterly reports on China's macroeconomic outlook have been presented and eleventh annual reports have been published. This 23rd quarterly report is to be presented at the Forum on China's Macroeconomic Outlook and Press Conference of CQMM on October 27, 2017. This conference is jointly held at Oxford University by Oxford Prospects and Global Development Centre, University of Oxford, Center for Macroeconomic Research at Xiamen University, and Economic Information Daily at Xinhua News Agency.